2010
DOI: 10.1007/s00253-010-2734-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical characterization of a nitrilase from the thermophilic bacterium, Geobacillus pallidus RAPc8

Abstract: Geobacillus pallidus RAPc8 (NRRL: B-59396) is a moderately thermophilic gram-positive bacterium, originally isolated from Australian lake sediment. The G. pallidus RAPc8 gene encoding an inducible nitrilase was located and cloned using degenerate primers coding for well-conserved nitrilase sequences, coupled with inverse PCR. The nitrilase open reading frame was cloned into an expression plasmid and the expressed recombinant enzyme purified and characterized. The protein had a monomer molecular weight of 35,79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…The 3D stain envelope was consistent with cyanide dihydratase from P. stutzeri , a member of the nitrilase superfamily [96,97]. Nitrilase from G. pallidus RAPc8 showed various structural forms, such as crescent-like, c-shaped, circular, and “figure-8” shapes through electron microscopy and image classification [59]. Far-UV circular dichroism (CD) spectroscopy was employed to determine the secondary protein structure of nitrilases from F. solani O1, and F. solani IMI 196840 [69].…”
Section: Introductionmentioning
confidence: 77%
“…The 3D stain envelope was consistent with cyanide dihydratase from P. stutzeri , a member of the nitrilase superfamily [96,97]. Nitrilase from G. pallidus RAPc8 showed various structural forms, such as crescent-like, c-shaped, circular, and “figure-8” shapes through electron microscopy and image classification [59]. Far-UV circular dichroism (CD) spectroscopy was employed to determine the secondary protein structure of nitrilases from F. solani O1, and F. solani IMI 196840 [69].…”
Section: Introductionmentioning
confidence: 77%
“…With one exception (PDB id: 3ILV, unpublished), the monomers pair to form αββα-αββα dimers ( Nakai et al, 2000 ; Pace et al, 2000 ; Wang et al, 2001 ; Kumaran et al, 2003 ; Kimani et al, 2007 ; Lundgren et al, 2008 ). Among members of the nitrilase branch of this superfamily, this basic dimer structure is expanded to form large spiral shaped homo-oligomers ( Sewell et al, 2003 , 2005 ; Thuku et al, 2007 ; Woodward et al, 2008 ; Dent et al, 2009 ; Williamson et al, 2010 ). The interaction between adjacent dimers in these spiral structures occurs at the C-surface and is proposed to be the primary contributor to spiral formation ( Sewell et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…While random mutagenesis and high throughput screening have revealed useful mutants ( Schreiner et al, 2010 ; Abou Nader, 2012 ; Wang et al, 2012 ), our ability to make rational changes is impeded by the absence of structural information of these enzymes. Three dimensional, negative stain electron microscopy (3D EM) has shown that many active nitrilases form large spiral shaped oligomers ( Jandhyala et al, 2003 ; Sewell et al, 2003 ; Thuku et al, 2007 ; Woodward et al, 2008 ; Dent et al, 2009 ; Williamson et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…PCC6803 (BA000022; Heinemann et al 2003) were used as references. Sequences for aromatic nitrilases were obtained from Rhodococcus rhodochrous J1 (D11425; Kobayashi et al 1992a), R. rhodochrous NCIMB 11216 (AX235749; Ress-Löschke et al 2001), and Aeribacillus pallidus RAPc8 (DQ826045; Williamson et al 2010). References for cyanide dihydratases were taken from Pseudomonas stutzeri AK61 (KM459551; Crum et al 2015), Bacillus pumilus C1 (AF492815; Jandhyala et al 2003), and B. pumilus 8A3 (AF492814; Jandhyala et al 2003).…”
Section: Construction Of a Phylogenetic Treementioning
confidence: 99%